Development of an in vivo mouse model of discogenic low back pain. Issue 10 (9th May 2018) - Shi, Changgui; Das, Vaskar; Li, Xin; Kc, Ranjan; Qiu, Sujun; O‐Sullivan, InSug; Ripper, Richard L.; Kroin, Jeffrey S.; Mwale, Fackson; Wallace, Atiyayein A.; Zhu, Bingqian; Zhao, Lan; et al.
Abstract : Discogenic low back pain (DLBP) is extremely common and costly. Effective treatments are lacking due to DLBP's unknown pathogenesis. Currently, there are no in vivo mouse models of DLBP, which restricts research in this field. The aim of this study was to establish a reliable DLBP model in mouse that captures the pathological changes in the disc and allows longitudinal pain testing. The model was generated by puncturing the mouse lumbar discs (L4/5, L5/6, and L6/S1) and removing the nucleus pulposus using a microscalpel under the microscope. Histology, molecular pathways, and pain‐related behaviors were examined. Over 12 weeks post‐surgery, animals displayed the mechanical, heat, and cold hyperalgesia along with decreased burrowing and rearing. Histology showed progressive disc degeneration with loss of disc height, nucleus pulposus reduction, proteoglycan depletion, and annular fibrotic disorganization. Immunohistochemistry revealed a substantial increase in inflammatory mediators at 2 and 4 weeks. Nerve growth factor was upregulated from 2 weeks to the end of the experiment. Nerve fiber ingrowth was induced in the injured discs after 4 weeks. Disc‐puncture also produced an upregulation of neuropeptides in dorsal root ganglia neurons and an activation of glial cells in the spinal cord dorsal horn. These findings indicate that the cellular and structural changes in discs, as well as peripheral and central nervous system plasticity, paralleled persistent, and robust behavioral pain responses. Therefore, this mouse DLBP model could be used to investigate mechanisms underlying discogenic pain, thereby facilitating effective drug screening and development of treatments for DLBP. Abstract : We have developed and validated a novel in vivo mouse model of discogenic pain. In this model, disc puncture with NP taken out induced progressive disc degeneration associated with pain behavior changes. We believe that this model can be used to investigate mechanisms underlying pathologic processes related to the development of discogenic pain.